Comparative statics for size-dependent discounts in matching markets - Delacretaz, D; Kominers, SD; Nichifor, A (Elsevier, 2020)
We prove a natural comparative static for many-to-many matching markets in which agents’ choice functions exhibit size-dependent discounts: reducing the extent to which some agent discounts additional partners leads to improved outcomes for the agents on the other side of the market, and worsened outcomes for the agents on the same side of the market. Our argument draws upon recently developed methods bringing tools from choice theory into matching.